(untitled) (ArtCultura, 2007)
Enxergado freqÃ¼entemente com lentes de aumento, o "Estado Novoâ€? â€” a julgar por muitos analistas â€” parece ter sido bem-sucedido na tentativa de moldar a sociedade brasileira à sua imagem e semelhança. Indo na contracorrente dessas análises, este texto envereda pelo mundo da canção popular produzida nessa época e busca captar vozes destoantes das falas oficiais, em especial no campo das relações de gênero. PALAVRAS-CHAVE: música popular; relações de gênero; "Estado Novoâ€?. ABSTRACT Frequently viewed through increasing lens, the so-called "Estado Novoâ€? â€” based on its many commentators â€” seems to have succeeded in its attempt at giving its own shape to the Brazilian society. Contrary to this view, this paper follows the way of the popular music written in Brazil at the time and searches to pick up voices inconsistent with the official ones, especially in the gender relationships domain. KEYWORDS: popular music; gender relations; "Estado Novoâ€? dictatorship.